The Influence of Smoothing Procedures on the Noise Reduction and Resolution Degradation of Scintigraphic Images - Gwiazdowska, A. Barbara; Skrzypczak, Ewa T.; Tolwinski, J. R. (Nuklearmedizin - NuclearMedicine, 1980)
The reduction of the statistical error and the decrease of the spatial resolution due to manyfold smoothing procedures applied to scintigraphic images were analysed. A quantitative relation was obtained between the characteristics of the error reduction factor kf, the resolution decrease factor kR and the linear size of the picture element m. The results showed that for the case of quasi-Gaussian smoothing matrices, e.g. manyfold smoothing, kR depends on the product of kf and m. Several numerical examples are given and discussed.